Futureproofing Assessment in Business Education: Lessons From COVID-19 - Barker , Sandra; Suri , Harsh; Gregory , Brent; Warner, Audrea; White , Amanda; Venkiteswaran , Vivek; Lightfoot, Una (Journal of Higher Education Theory and Practice, 2021)
The recent COVID-19 pandemic crisis required Business Schools to quickly reconsider all assessment methods, particularly the use of face to face invigilated exams. With lockdown and physical distancing requirements requiring teaching and learning activities to move to online mode, the need to consider alternate technology enabled assessments and how they could be implemented quickly and effectively became a crucial focus of universities in early 2020, affecting staff and students alike. This paper considers the experiences of a group of academics and academic developers from five ANZ Business Schools and the lessons that they learnt from these experiences.